(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Mental health itself is a topic that is not considered as important as physical health in our our society but men’s mentalhealth is at even worse position not only in our country but around the world. Firstly, mental health issues among men are often overlooked or stigmatized due to societal expectations of masculinity that discourage vulnerability and help-seeking behaviors. This can lead to an exacerbation of mental health problems and reluctance to seek treatment, resulting in adverse consequences for individuals, families, and communities. Secondly, mental health conditions in men can manifest differently than in women, and there may be unique risk factors and barriers to access appropriate support services. Understanding these nuances is essential for developing effective prevention, diagnosis, and treatment strategies tailored to men's specific needs. Furthermore, ignoring men's mental well-being has significant societal implications, including increased rates of substance abuse, violence, unemployment, and suicide. By prioritizing research and awareness efforts, we can break down stigmas, promote early intervention, and improve overall public health outcomes. Ultimately, studying men's mental health is a step towards fostering a more inclusive and supportive environment where all individuals, regardless of gender, can address their psychological needs without fear or judgment.